Diagnóstico de la eficiencia energética en el proceso de molienda de productos deshidratados, con molino de martillos, en la industria aromas de Tungurahua en la ciudad de Ambato. Diseño de un sistema automatizado de control de velocidad de alimentación del producto. - Silva Monteros, Franklin Manuel (2016)
The Industry of Aromas del Tungurahua, into several of its processes is the grinding of dried products using a hammer mill, the feed rate of the product is chosen according to the product and the people experience that run the milling process. While experience allows the operating point be good, is not optimal, so it is necessary to determine the optimum feed rate of the product and its impact on energetic efficiency, so that the unawareness in it take account in the productivity, it has a consumption in excess of electrical energy and the effectiveness and competitiveness of the company is affected. The design of an automated speed control system to monitor the feed rate of the product by means of variable speed drives and Programmer Logic Controllers let to improve energetic efficiency and maintain the optimal operating point. To characterize the process and determine correctly the type of automation required, several grindings are performed by measuring their weight, power consumption, the time used and the quality obtained, until finding the speed that provides the greatest benefits, for this reason it is used a empiricist-inductive approach. Then for automatic design it is applied a rationalist-deductive approach.